Verbo-pictorial metaphor in French advertising. Issue 2 (July 2014) - ALOUSQUE, ISABEL NEGRO
ABSTRACT In the last thirty years the development of the Cognitive Metaphor Theory (e.g. Lakoff, 1987, 2006; Lakoff and Johnson, 1999) has led to vast research into metaphor. The study of linguistic metaphor was followed by a body of work into pictorial metaphor (Forceville, 1994, 1996) and multimodal metaphor (Forceville, 2007, 2008, 2009). In the present contribution we explore the use of verbo-pictorial metaphors in advertising through a corpus of French print ads. Starting from the claim that adverts serve a persuasive purpose, it will be argued that multimodal metaphor contributes to that purpose. The paper addresses three issues: a) how multimodal metaphors are manifested in the French advertisements; b) how image and text interact in a concrete type of multimodal metaphor in French print advertisements, namely verbo-pictorial metaphor; c) how verbo-pictorial metaphor performs a pragmatic function in advertising.